Comprehensive N-glycosylation profiling of recombinant spike S1 protein from the wild-type SARS-CoV-2 and its variants - Peng, Yao; Tong, Tian-Tian; Deng, Qiu-Yu; Yau, Lee-Fong; Qiu, Jia-Qi; Zhao, Qing; Wu, Jia-Qi; Xin, Zhi-Qiang; Guan, Man-Ci; Li, Yue; Jiang, Zhi-Hong; Pan, Hu-Dan; et al. (Frontiers in Immunology, 2025)
IntroductionBy 2024, COVID-19 has become endemic, with new variants contributing to its continued spread. The Spike protein forms trimers that bind to the ACE2 receptor on host cells, with the S1 subunit being a primary target for vaccines and antiviral treatments.MethodsHerein, we performed an in-depth analysis of the N-glycosylation of the recombinant Spike S1 protein (S1 protein) across the wild-type (WT) virus and its 5 variants, including Alpha, Beta, Gamma, Delta, and Lambda, by integrating ultrahigh-performance liquid chromatography coupled with quadrupole-time-of-flight mass spectrometry (UHPLC-Q-TOF MS) and unique TiO₂-PGC chip-based LC/MS techniques.ResultsA total of 332 glycan structures arising from 180 compositions on the S1 and RBD regions were identified, revealing remarkable glycosylation diversity of the S1 protein. Complex glycan was shown to be the dominant structure across variants. Neutral N-glycans are mainly di-antennary with two fucosyl groups, while the majority of acidic N-glycans were multi-antennary with mono-fucosyl residues. In addition, sialic acid linkages of the N-glycans were extensively studied by utilizing ¹³C-labeled standards and specific enzymes for the first time, showing the existence of both α-2,3 and α-2,6 linkages across WT and five variants. It should be noted that the Lambda variant shows more complex α-2,3 and α-2,6-linked glycans in the RBD region, which may potentially enhance its glycan shield effect. Acetylated glycans, which were identified on S protein for the first time, were found to be fully fucosylated on the S1 region and sialylated on the RBD region across all variants. UHPLC-TOF MS analysis revealed unoccupied N-glycosylation sites in S1-Gamma (N657), S1-Delta (N61), and S1-Lambda (N17, N61, N657), with N17 and N61 showing low glycan occupancy (0%-3.4%), suggesting these sites may lack glycan shield protection.DiscussionThis study provides a comprehensive N-glycosylation profile of the S1 protein across different variants, offering an essential structural basis for future vaccine development and research on viral functions.